The New Formulations of Immunoglobulin Replacement Therapies and Future Aspects - Elif Karakoç-aydıner (Turkish Journal of Immunology)
Immunoglobulin replacement therapy (IgRT) stands as the established method of treatment for numerous inborn errors of immunity (IEI). Over the past six decades, there have been notable advancements in the dosing, processing, and administration routes of IgRT for IEI. Intravenous immunoglobulin has proven to be an effective treatment method, typically administered every 3 to 4 weeks. Traditional subcutaneous intravenous immunoglobulin (SCIG) is equally effective in maintaining biological IgG levels, with smaller doses administered daily every 2 weeks. F-SCIG is also equally effective and is typically administered every 3 to 4 weeks, in which patients are first required to administer hyaluronidase and then the gammaglobulin. Compared to less concentrated SCIG products, those with higher concentrations allow for the infusion of a smaller volume, less time spent on infusion, increased interval between infusions, and improved health-related quality of life. In addition, high-concentration products are reported to be similarly effective and well-tolerated by patients compared to lower-concentration SCIG and IVIG bioequivalents. High-concentration SCIG products, such as Cutaquig/Gammanorm (16.5% IgG) and Hizentra, Cuvitru, and Xembify (20% IgG), are available in the market. Overall results demonstrated that high-concentration SCIG products were efficient and well-tolerated, and allowed successful self-administration in individuals with IEI. A precise and personalized approach to IgRT is essential for improving outcomes in patients with IEI. The quest for new IgRT formulations and improved ancillary tools for SCIG aims to lower the occurrence of infections and complications related to them by enhancing adherence to long-term IgRT.